Expression and Function Analysis of Interleukin-17A/F1, 2, and 3 Genes in Yellow Catfish (Pelteobagrus fulvidraco): Distinct Bioactivity of Recombinant IL-17A/F1, 2, and 3 - Zhou, Xu; Zhang, Gui-Rong; Ji, Wei; Shi, Ze-Chao; Ma, Xu-Fa; Luo, Zun-Lan; Wei, Kai-Jian (Frontiers in Immunology, 2021)
In mammals, Interleukin-17 cytokine family plays critical roles in both acute and chronic inflammatory responses. In fish species, three Interleukin-17A/F (IL-17A/F) genes have been identified to be homologous to mammalian IL-17A and IL-17F, but little is known about their functional activity. In this study, Pf_IL-17A/F1, 2 and 3 genes were cloned from yellow catfish (Pelteobagrus fulvidraco) and they differed in protein structure and exon length, implying that they may have divergent bioactivity. Real-time quantitative PCR analyses revealed that three Pf_IL-17A/F genes were highly expressed in blood and mucosal tissues (skin+mucus and gill) from healthy adult fish. The mRNA expressions of Pf_IL-17A/F1, 2 and 3 genes were significantly up-regulated in the gill, skin+mucus, head kidney and spleen after challenge with Edwardsiella ictaluri and in the isolated peripheral blood lymphocytes (PBLs) of yellow catfish after stimulation with phytohaemagglutinin (PHA), lipopolysaccharides (LPS), peptidoglycan (PGN) and polyinosinic-polycytidylic acid (Poly I:C). These results indicate that Pf_IL-17A/F1, 2 and 3 genes may play a vital role in the regulation of immune against pathogens. Additionally, the rPf_IL-17A/F 2 and 3 proteins promoted phagocytosis of PBLs more powerfully than the rPf_IL-17A/F1, while the rPf_IL-17A/F1 elicited the most potent chemotaxis of PBLs, and the rPf_IL-17A/F1, 2 and 3 proteins significantly induced the mRNA expressions of antibacterial peptides genes. Furthermore, the rPf_IL-17A/F1, 2 and 3 proteins might activate the NF-κB and MAPK signal pathways by IL-17RA, ACT1, TRAF6, TRAF2, TRAF5 and TAK1, indicating that the three Pf_IL-17A/F proteins may play different roles in promoting inflammatory response.